ALLogeneic Heart STem Cells to Achieve Myocardial Regeneration (ALLSTAR) Trial: Rationale and Design. Issue 2 (February 2017) - Chakravarty, Tarun; Makkar, Raj R.; Ascheim, Deborah D.; Traverse, Jay H.; Schatz, Richard; Demaria, Anthony; Francis, Gary S.; Povsic, Thomas J.; Smith, Rachel R.; Lima, Joao A.; Pogoda, Janice M.; Marbán, Linda; et al.
Autologous cardiosphere-derived cells (CDCs) were the first therapeutic modality to demonstrate myocardial regeneration with a decrease in scar size and an increase in viable, functional tissue. Widespread applicability of autologous CDC therapy is limited by the need for patient-specific myocardial biopsy, cell processing, and quality control, resulting in delays to therapy and inherent logistical and economic constraints. Preclinical data had demonstrated equivalent efficiency of allogeneic to autologous CDCs. The ALLogeneic Heart STem Cells to Achieve Myocardial Regeneration (ALLSTAR) trial is a multicenter randomized, double-blind, placebo-controlled phase 1/2 safety and efficacy trial of intracoronary delivery of allogeneic CDCs (CAP-1002) in patients with myocardial infarction (MI) and ischemic left ventricular dysfunction. The phase 1 safety cohort enrolled 14 patients in an open-label, nonrandomized, dose-escalation safety trial. The phase 2 trial is a doubleblind, randomized, placebo-controlled trial that will compare intracoronary CDCs to placebo in a 2:1 allocation and will enroll up to 120 patients. The primary endpoint for both phases is safety at 1 month. For phase 2, the primary efficacy endpoint is relative change from baseline in infarct size at 12 months, as assessed by magnetic resonance imaging. The ALLSTAR trial employs a "seamless" WOVE 1 design that enables continuous enrollment from phase 1 to phase 2 and will evaluate the safety of intracoronary administration of allogeneic CDCs and its efficacy in decreasing infarct size in post-MI patients.